2022
DOI: 10.1097/iae.0000000000003373
|View full text |Cite
|
Sign up to set email alerts
|

Double Fluence Photodynamic Therapy for the Treatment of Circumscribed Choroidal Hemangioma

Abstract: Double-fluence photodynamic therapy is an effective and safe procedure to treat circumscribed choroidal hemangioma and its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Otherwise, in the case of multispot treatment, overlapping spots have historically been avoided due to the theoretical risk of increased side effects [ 11 ]. A 2014 study conducted by Su et al [ 3 ] showed no complications in overlapping treatment at the conventional 50 J/cm 2 light dose compared to single spot treatment, and more recent studies have suggested the superiority of the double-fluence protocol with 100% tumor regression and SRF resolution after a single treatment session with no need for retreatment, whereas previous cases utilizing the standard protocol showed retreatment rates of 12–80% of cases [ 3 , 8 , 12 ]. Notably, choroidal ischemia and atrophy have typically been reported in cases requiring three or more sessions of PDT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, in the case of multispot treatment, overlapping spots have historically been avoided due to the theoretical risk of increased side effects [ 11 ]. A 2014 study conducted by Su et al [ 3 ] showed no complications in overlapping treatment at the conventional 50 J/cm 2 light dose compared to single spot treatment, and more recent studies have suggested the superiority of the double-fluence protocol with 100% tumor regression and SRF resolution after a single treatment session with no need for retreatment, whereas previous cases utilizing the standard protocol showed retreatment rates of 12–80% of cases [ 3 , 8 , 12 ]. Notably, choroidal ischemia and atrophy have typically been reported in cases requiring three or more sessions of PDT [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…protocol showed retreatment rates of 12-80% of cases [3,8,12]. Notably, choroidal ischemia and atrophy have typically been reported in cases requiring three or more sessions of PDT [8].…”
Section: Case Reports In Ophthalmologymentioning
confidence: 99%
“…There are a variety of indications for PDT with verteporfin that include the treatment of choroidal neovascularization in myopia, age-related macular degeneration, and presumed ocular histoplasmosis syndrome, as it offers selective laser stimulation of choroidal vascularized structures [9][10][11][12]. In CCH, PDT is considered the primary line of management modalities using a variable number of protocols that vary in timing of infusion, dosages, levels of energy, timing of application of laser, spot sizes, single or overlapping spots, and repeating or not repeating the treatment [3,13].…”
Section: Introductionmentioning
confidence: 99%